Religious Identity Politics In Indonesia's 2019 Election Campaign On Twitter And Its Socio-Political Implications - Prayogi, Danu; Fahadayna, Adhi Cahya (Pusat Riset Politik BRIN, 2023)
This paper explains the use of hate spin as a tool of identity politics in the presidential elections 2019 on Twitter by hate spin agents. Used CherianGeorge's hate spin concept, which includes tactical flexibility, distributed efforts, and symbolic contention, and the tweets were analyzed using sentiment analysis. According to the findings of sentiment analysis, three variables are being leveraged by hate spin agents on Twitter during the 2019 presidential election campaign. After training test data, tweets were dominated by negative sentiment; tweets with hashtag abundant resulted in 807 negative and 323 positive, with a Naïve Bayes model of 0.995 (99.5%). Hate spin campaigns have negative consequences for Indonesia and the country's democracy because they foster sharp differences and intolerance toward the identities of other groups, causing societal divisions that have the potential to lead to identity conflict, genocide, or national division if not managed well and taken seriously by the government and the nations itself.